Building Independent Villages through Collaborative Governance by Village-Owned Enterprises (Best Practice from Panggungharjo Village, Central Java, Indonesia) - Sri Juni Woro Astuti; Falih Suaedi (Journal Ilmu Sosial, Politik dan Pemerintahan, 2018)
This study aims to develop a collaborative governance model applied by village-owned enterprises called "BUMDes" which has become one of the keys to the success of the village government in improving the economy and welfare of rural communities becoming an independent village. The research method used is descriptive qualitative method with a case study approach that is by taking the setting and research focus on the success of BUMDes in the village of Panggungharjo, Bantul Regency, Central Java Province. Primary data collection was carried out through in-depth interviews with several key informants and supporting informants, which were determined by snowball sampling. The main informants consisted of: the village head, the head of the village deliberation body, and the village secretary who then rolled out to several supporting informants consisting of the BUMDes officials, community leaders, and the private sector who collaborated with the Panggungharjo BUMDes. In addition, secondary data needed is obtained through documentary studies. This research will produce a collaborative governance model that is expected to be used as a reference for the management of other BUMDes in Indonesia.